2022
DOI: 10.1177/15589447221093668
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Nerve Block Diminishes the Effects of Therapeutic Electrical Stimulation to Enhance Nerve Regeneration in Rats

Abstract: Background: Although electrical stimulation (ES) can improve nerve regeneration, the impact of nerve block, such as lidocaine (Lido), on the therapeutic benefits of ES remains unclear. We used a rat tibial nerve transection-and-repair model to explore how either preoperative (PreOp) or postoperative (PostOp) nerve block affects ES-related improvement in regeneration. Methods: Lewis rats were used in 1 of 2 studies. The first evaluated the effects of extraneural Lido on both healthy and injured nerves. In the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Electrical stimulation (ES) of muscles is a standard manipulation by physiotherapists aiming to prevent denervation atrophy and joint fixation [ 16 , 17 ]. In contrast, ES for injured nerves has been a more recent approach to promote muscle and sensory reinnervation [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], and these findings of Brushart and Gordon are largely confirmed by many investigators [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. This review considers (1) how and why functional recovery is poor after peripheral nerve injury, and (2) the efficacy of neurotrophic factors and/or brief low-frequency ES to counteract the negative effects of delayed surgical repair as a prelude to advocate ES to promote nerve regeneration and functional recovery after human nerve injuries.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Electrical stimulation (ES) of muscles is a standard manipulation by physiotherapists aiming to prevent denervation atrophy and joint fixation [ 16 , 17 ]. In contrast, ES for injured nerves has been a more recent approach to promote muscle and sensory reinnervation [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], and these findings of Brushart and Gordon are largely confirmed by many investigators [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. This review considers (1) how and why functional recovery is poor after peripheral nerve injury, and (2) the efficacy of neurotrophic factors and/or brief low-frequency ES to counteract the negative effects of delayed surgical repair as a prelude to advocate ES to promote nerve regeneration and functional recovery after human nerve injuries.…”
Section: Introductionmentioning
confidence: 83%
“…The efficacy of ES in promoting nerve regeneration [ 20 , 21 , 22 , 23 , 24 ] has been confirmed [ 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] and reviewed [ 53 , 56 , 57 , 58 , 59 , 60 , 61 ]. There are additional studies demonstrating that ES (1) accelerates nerve regeneration through a nerve isograft of 10 mm in Lewis rats [ 46 ] and through 10 and 20 mm nerve autografts in Sprague-Dawley rats [ 47 ], (2) increases the number of macrophages and neutrophils in the denervated distal nerve stumps as well as the number of M2 macrophages within autografts [ 46 , 50 ], (3) shifts the macrophage phenotype in a locally demyelinated peripheral nerve from the proinflammatory M1 toward the predominantly pro-repair M2 type [ 338 ], (4) accelerates Wallerian degeneration and upregulates BDNF and NGF in denervated SCs [ 339 ], and (5) together with testosterone administration promotes facial nerve regeneration and functional recovery of whisking and blink reflexes after crush injury in castrated male rats [ 33 , 36 ] in association with a more rapid and sustained upregulation of BDNF than either alone [ 36 ].…”
Section: Neuronal Activity and Nerve Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2000, Al-Majed et al demonstrated that the application of tetrodotoxin, a voltage-gated sodium channel blocker, to a repaired nerve, eliminated the pro-regenerative effects of ES by blocking retrograde action potential propagation [ 17 ]. A recent study by Keane et al found that the administration of perioperative lidocaine significantly diminished the ES-related improvement in nerve regeneration ( Figure 3 ) [ 105 ]. The interaction between ES and peripheral nerve blocks is critical to recognize when designing clinical trials [ 105 ].…”
Section: Electrical Stimulation and Peripheral Nerve Blocksmentioning
confidence: 99%
“…A recent study by Keane et al found that the administration of perioperative lidocaine significantly diminished the ES-related improvement in nerve regeneration ( Figure 3 ) [ 105 ]. The interaction between ES and peripheral nerve blocks is critical to recognize when designing clinical trials [ 105 ]. These results suggest that general anesthesia must be used when using ES during peripheral nerve repair.…”
Section: Electrical Stimulation and Peripheral Nerve Blocksmentioning
confidence: 99%